Microfabrication and characterization of gridded polycrystalline silicon field emitter devices - Huq, SE; Huang, M; Wilshaw, P; Prewett, P (1998)
Uniform arrays of sharp polysilicon held emitters have been fabricated in gridded configuration using state of the art microfabrication techniques including high resolution electron beam lithography and plasma dry etching. Emission currents up to 2.5 mu A/tip have been obtained at a 90 V grid-bias. Preliminary Lifetime measurements (14 h continuous operation) have been carried out under ultrahigh vacuum conditions. (C) 1998 American Vacuum Society. [S0734-211X(98)04602-2].